Detection of Mycobacterium avium subsp. paratuberculosis in bulk tank milk by combined phage-PCR assay: Evidence that plaque number is a good predictor of MAP - Botsaris, George; Liapi, Maria; Kakogiannis, Charalambos; Dodd, Christine E R; Rees, Catherine E.D. (My University, 2013)
Conventional culture and a rapid phage-PCR method were used to detect Mycobacterium avium subsp. paratuberculosis (MAP) in bulk tank milk (BTM) samples. Only two of 225 samples (0.9%) were found to contain MAP by culture whereas 50 (22%) MAP-positive samples were identified using the phage-PCR assay, including both samples that were MAP-culture positive. Results using the phage-based method for independently tested duplicate samples indicated that the assay is very reproducible (r2=0.897), especially when low levels of mycobacteria are present. A relationship was established between plaque number and the presence of MAP in a sample. A cut-off value was determined allowing identification of MAP-positive samples based on plaque number alone (90% sensitivity, 99% specificity; area under the curve=0.976). These results indicate that the assay is a robust method for screening BTM, providing results within 24h.
Keywords: Detection; Milk; Paratuberculosis; Phage-PCR assay